Academic Integrity in the Context of European Experience and Ukrainian Practice - Dorozhko, Anastasiia (Educational Challenges, 2022)
The article analyses the experience of European countries in counteraction to academic dishonesty and plagiarism, as well as the attitude of Ukrainian students to the problem. The specific examples of the counteraction against academic fraud in universities abroad have been studied, in particular, in the United Kingdom at the University College London, in Sweden at the Karolinska Medical University, and in higher education institutions in Poland. The article examines the attitude of Ukrainian students to various issues of academic integrity by questionnaires for its development in higher education institutions to prevent plagiarism in Master’s theses. The purpose of the research is to study the European experience in counteraction to the manifestations of academic dishonesty and plagiarism among students to apply the experience in Ukrainian higher education institutions. Methodology. A survey among Master’s students in H.S. Skovoroda Kharkiv National Pedagogical University was conducted, which revealed the level of students’ knowledge about such concepts as academic integrity, plagiarism, as well as its types and reasons that motivate students to academic dishonesty and plagiarism. Results. The results of the survey show that, unfortunately, most students do not consider plagiarism a fraud. According to them, posting a text on the Internet makes it common and accessible to all, “nobody’s”, and academic dishonesty and plagiarism in the student environment by majority of students is still perceived as the norm. Conclusions. To develop the academic integrity for Ukrainian students, it is necessary to implement a set of various measures. Promoting academic integrity and counteraction to plagiarism should take place at the level of the national ministry, higher education institutions, University faculties, departments, teaching staff, and the students themselves. Such work must be systematic, have a strategy, technology, ways of implementation at all levels of the scientific and educational process. It is expedient to conduct mass, explanatory, preventive work in each university, instill in Ukrainian students the principles of academic integrity, conduct special lessons to prevent plagiarism, work with common electronic programs of text self-checking, and teach training modules.